Growth performance of African catfish (Clarias gariepinus) juvenile fed cattle hoof meal reference and test diets. - Eyiwunmi, Falaye Augustine; Shakiru, Sule Okanlawon (Universitas Malikussaleh, 2022)
Cattle hoof meal was processed by autoclaving, fermentation, wood ash fermentation, soda ash treatment and raw-unprocessed hoof. This was studied on Clarias gariepinus juveniles 14.22±0.23g stocked at 15 fish per tank in replicate. Treated samples were used in compounding six isonitrogenous diets of a reference diet 70%: test diet 30% and fed at 3% body weight. Significant difference (P<0.05) was observed among dietary treatments. Weight gain, specific growth rate feed conversion ratio percentage weight gain in soda ash diet was enhanced followed by raw hoof diet while wood ash treated diet showed the least response on fish growth. Fish carcass quality was enhanced with raw hoof treated diets over other diets. Utilization of soda ash treated hoof meal can be used in enhancing growth of C. gariepinus.Keywords: Fishmeal, Cattle-hoof-meal, haematology, keratin.